Unveiling reverse vaccinology and immunoinformatics toward Saint Louis encephalitis virus: a ray of hope for vaccine development - Ramalingam, Prasanna Srinivasan; Aranganathan, Mahalakshmi; Hussain, Md Sadique; Elangovan, Sujatha; Chellasamy, Gayathri; Balakrishnan, Purushothaman; Mekala, Janaki Ramaiah; Yun, Kyusik; Arumugam, Sivakumar (Frontiers in Immunology, 2025)
IntroductionInfectious diseases continue to challenge human health with high incidence and mortality rates worldwide. Notably, the adaptability of RNA viruses, highlighted by outbreaks of SARS, MERS, and COVID-19, emphasizes the timely need for effective therapeutics. Saint Louis encephalitis virus (SLEV) belonging to the Flaviviridae family is an RNA virus that mostly affects the central nervous system (CNS) of humans. Although supportive care treatments such as antiemetics and painkillers are being used against SLEV infection, it still lacks potential therapeutics for the effective treatment.MethodsReverse vaccinology and immunoinformatics approaches help in the identification of suitable epitopes to design a vaccine construct that will activate both B- and T-cell-mediated responses. Previous studies used only the envelope protein E for the vaccine design, but we have used multiple protein targets to enhance the vaccine efficacy. Thus, in the present study, we have designed a multi-epitope subunit vaccine that specifically targets the membrane glycoprotein M, envelope protein E, and anchored capsid protein anchC of SLEV.ResultsOur results indicated that the vaccine construct is structurally stable, antigenic, non−allergic, non−toxic, and soluble. Additionally, the vaccine construct was structurally refined and indicated significant binding affinity toward the Toll-like receptor 4 (TLR-4) supported by molecular docking and molecular dynamics simulations. Furthermore, it also indicated that it has the potential to induce an immune response.ConclusionIn addition, it has been cloned in the pET-28a (+) vector-6xHis-TEV-ORF9c expression vector for further experimental validation. We also recommend to evaluate the designed vaccine’s therapeutic efficacy through in vitro and in vivo studies in the near future.